DESAIN MESIN SANGRAI KOPI DENGAN MENGGUNAKAN SENSOR THERMOCOUPLE KAPASITAS 2KG UNTUK PENINGKATAN PENDAPATAN USAHA UMKM DI KEC. NAMAN TERAN - Arya Rudi Nasution; Khairul Umurani; Affandi; Muhammad Refan (CERED Indonesia Publishing, 2023)
Occupational safety and health are the most important factors in work because they can encourage productivity, which leads to the welfare of all parties, both employers and workers. One way to avoid work accidents and health problems for workers is to use personal protective equipment and production equipment that supports the processing of food and beverage ingredients (coffee beans). Coffee is an agricultural commodity that is used as a raw material for the food and beverage industry. In Kuta Rayat Village, Namanteran District, Karo Regency, there are household businesses and MSMEs roasting coffee beans, consisting of 2 to 3 Small and Medium Enterprises (MSMEs). The process of roasting coffee beans is done manually, so businesses still produce it on a small scale. The roasting process is carried out by roasting tubes that are rotated manually by Mr. Muhammad Iksan Ginting, which can cause harm to the health of business actors as well as roasting results that are not optimal. The roasting process is the process of forming the taste and aroma of coffee beans. If the coffee beans have a uniform size, specific gravity, texture, moisture content, and chemical structure, then the roasting process will be relatively easier to control. The reality is that coffee beans are so different that the roasting process is an art and requires as much skill and experience as consumer demands. Therefore, based on the problems encountered, it is necessary to design tools that can support the product production process. Coffee Roasting Machine With Smart Phone Control System 2kg Capacity.